PRESERVATION AND USE OF ARCHAEOLOGICAL HERITAGE IN WEST SIBERIA - C.С. Тихонов (Теория и практика археологических исследований, 2021)
Archaeological sites are the only source of information on the preliterate period in the history. In West Siberia and further to the east of the Ural mountains written sources appear only after arrival of Russians at the end of the 26th century. Therefore, the value of archaeological materials in studying of pre-Russian Siberia cannot be overestimated. Therefore, the effective system of protection and using of archaeological heritage of natives of Siberia is necessary. The special federal law is directed on it. However, in practice of archeologists there are nuances which the legislation does not regulate.This situation is analyzed by the author of article. First of all, this is due to the fact that it is advisable to excavate archaeological sites in those regions that have been most developed. This is due to both the significance of the sites, its accessibility, and the cost of archaeological work. Hundreds of interesting objects have been excavated, but the materials of many are unpublished, which hinders the growth of the available source base. However, the obligation to introduce the materials into scientific circulation in a timely manner is not imposed on researchers. I particularly note the inattention to the publications of organizations that conduct rescue and new-build archaeological work. The second aspect is related to the ncreasing attention of Russian citizens to antiquities, which they often find during trips. It is impossible to say how many such finds are eventually lost. The situation could be corrected by the interaction of the sites protection bodies, museum institutions and citizens. However, it happens that it is easier for citizeno throw away a find than to carry it to a cultural institution. This situation requires a legislative solution.